The ultimate ChatGPT guide with React Native : develop mobile apps. (Packt Publishing, 2023)
This course is designed with the latest mobile technology and in-demand job tools including React Native, JavaScript, Expo-GO, and the best conventions in 2023; it also teaches the very latest mobile development techniques and version of React with hooks. This course demonstrates how to leverage the power of ChatGPT as a tool in addition to stack overflow and documentations to build scripts and simplifies tackling difficult code tasks and takes your coding skills to the next level. Here, you will code along with ChatGPT and develop a project from scratch for your portfolio. You will learn how to develop professional web applications with ChatGPT and modern tools and libraries including React Native and JavaScript. Look at the object-oriented programming and functional components in React and React Hooks. You will explore the art of professional coding techniques building a sleek and functional UI. You will see how to write code with templated models and libraries, and clearly document your thought process. Finally, you will learn how to build and work on an entire mobile application with a client-side, simulated database with ChatGPT and enhance your productive levels as a programmer. By the end of the course, you will have deployed an application to your phone with real functionality. What You Will Learn Create a simulated database using ChatGPT Learn to render data on the page using best practices Look at how to use ChatGPT to create realistic simulations Implement features such as likes, comments, stories, and users Learn OOP and functional components in React and React Hooks Create a visually appealing and easy-to-navigate user interface Audience This course is perfect for those who want to gain confidence in mobile app development using ChatGPT and have a basic understanding of JavaScript. It's a great starting point for beginners interested in programming and a valuable addition to the portfolio of those pursuing a career in the industry. While prior knowledge of JavaScript and web development would be advantageous, it is not a prerequisite as the course is designed to cater to learners with no programming experience. About The Author Clarian North: Clarian North is a recognized industry-certified instructor, CEO of Orbital LLC, and a senior project engineer with over 90K enrolments worldwide. His students have gone on to work for some of the biggest production companies such as Universal, Google, Amazon, Warner, and BBC. He has contributed to viral streams, grown a unique digital imprint in over 80 countries, and has been featured in Rolling Stone, Billboard, Guardian, Bloomberg, and Vice. He has worked for majors, indies, and international publishing houses, including Grammy-nominated and award-winning productions, mixing for Emirates Airline Inflight Radio, and producing for Kompakt Records. He is dedicated to giving accessible and comprehensive tech courses, teaching complex subject matter with clear and example-based explanations, and guiding students through complex techniques with just a computer and free software.